2010
DOI: 10.1111/j.1755-3768.2010.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal sensitivity and fixation changes 1 year after triamcinolone acetonide assisted internal limiting membrane peeling for macular hole surgery – a MP‐1 microperimetric study

Abstract: Purpose: To evaluate microperimetric changes 1 year after macular hole surgery with triamcinolone acetonide assisted internal limiting membrane (ILM) peeling. Methods: Twenty-two eyes of 22 patients with stage 3 and 4 idiopathic macular holes of <6 months' duration underwent vitrectomy with triamcinolone acetonide assisted ILM peeling. Best corrected visual acuity (BCVA) (logarithm of the minimum angle of resolution), and central retinal sensitivity were documented before and 1, 3, 6, and 12 months after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…Ozdemir et al [7] have also shown retinal sensitivity and fixation changes seen one year after ILM peeling for macular hole surgery using MP-1 micro perimetric study. Study showed postoperatively, there was a shift in the position of fixation point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozdemir et al [7] have also shown retinal sensitivity and fixation changes seen one year after ILM peeling for macular hole surgery using MP-1 micro perimetric study. Study showed postoperatively, there was a shift in the position of fixation point.…”
Section: Discussionmentioning
confidence: 99%
“…This comprehensive evidence by Pichi et al [1] appears to suggest that ILM peeling is traumatic and may have acute effects on nerve fiber layer. Focal ERG and micro perimetry studies suggest the role of Muller cell damage, reduced retinal sensitivity and incidence of micro-scotomas [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Вестник офтальмологии 6,2016 ложили, что основным источником аберраций яв-ляются изменения формы роговицы, а отсутствие СТ не влияет на аберрации. Выявлено, что наложе-ние швов в области склеральных портов приводит к возникновению роговичного астигматизма, за-трагивающего как переднюю, так и заднюю по-верхность роговицы.…”
Section: обзор литературыunclassified
“…Однако, не-смотря на эффективность данного метода лечения, его применение может стать причиной ряда струк-турно-функциональных изменений различных отде-лов глазного яблока. В современной специальной литературе подробно освещены вопросы подобных нарушений заднего отрезка глаза после витрэктомии [5,6]. Однако указанные изменения, наблюдаемые в проекции пространства переднего отрезка глаза, из-учены недостаточно.…”
unclassified